ANAMMOX performance, granulation, and microbial response under COD disturbance. Issue 1 (13th February 2014) - Li, Yuan; Huang, Zhenxing; Ruan, Wenquan; Ren, Hongyan; Zhao, Mingxing
Abstract BACKGROUND ANAMMOX (ANaerobic AMMonium OXidation), a promising process for biological nitrogen removal, is usually affected by organic matter. In order to fully understand the effect of chemical oxygen demand (COD) on the ANAMMOX process, reactor performance, granular characteristics and microbial response were evaluated systematically under glucose stimulation. RESULTS High removal efficiencies of ammonium and total nitrogen (> 90%) were achieved with 100 mg L‐1 COD concentration. ANAMMOX contribution was reduced to only 69% as COD concentration was increased to 300 mg L‐1. The granulation, EPS contents, TB‐EPS/LB‐EPS and protein/carbohydrate were increased at a specific COD, with higher COD disrupting the biofacies structure. The results also showed that EPS distribution and microbial structure were affected by the organic disturbance. CONCLUSION An appropriate COD concentration enhanced the total nitrogen removal during ANAMMOX process, by enabling a stable synergism between ANAMMOX bacteria and heterotrophic denitrificans. Furthermore, a proper COD stimulation promoted sludge granulation by influencing EPS composition and distribution. However, excessive COD disturbance disrupted the highly efficient biofacies structure and microbial balance, which then decreased the ANAMMOX competitiveness. © 2013 Society of Chemical Industry